Inhibition of DRP-1-Dependent Mitophagy Promotes Cochlea Hair Cell Senescence and Exacerbates Age-Related Hearing Loss - Lin, Hanqing; Xiong, Hao; Su, Zhongwu; Pang, Jiaqi; Lai, Lan; Zhang, Huasong; Jian, Bingquan; Zhang, Weijian; Zheng, Yiqing (Frontiers in Cellular Neuroscience, 2019)
Abstract Background: Mitochondrial dysfunction is considered to contribute to the development of age-related hearing loss (AHL). The regulation of mitochondrial function requires mitochondrial quality control, which includes mitophagy and dynamics. In such regulation, DRP-1 (Dynamin-related Protein 1) is believed to play a central role. However, the underlying mechanism of DRP-1 in AHL remains unclear. Here we examined whether the decline of DRP-1-dependent mitophagy contributes to the development of AHL. Methods: We induced cellular and cochlear senescence by hydrogen peroxide (H2O2) and evaluated senescent level by senescence associated β‐galactosidase stain. We evaluated mitophagy levels by fluorescence image and Western Blotting of LC3II and P62. Mitochondrial function was assessed by ATP assay, mtDNA assay and JC-1. Results: We found that both the expression of DRP-1 and the mitophagy level decreased in senescent cells and aged mice. DRP-1 overexpression in HEI-OC1 cells initiated mitophagy and preserved mitochondrial function when exposed to H2O2, meanwhile cells with DRP-1 silencing displayed otherwise. Moreover, inhibition of DRP-1 by Mdivi-1 blocked mitophagy and exacerbated hearing loss in aged C57BL/6 mice. Conclusion: These results indicated that DRP-1 initiated mitophagy, eliminated mitochondrial dysfunction, and may protect against oxidative stress-induced senescence. These results provide a potential therapeutic target for age-related hearing loss.